SUPERVISI AKADEMIK DALAM UPAYA PEMBINAAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN ANAK USIA DINI (PAUD) - Eka Rista Harimurti (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2019)
This article aims to provide an overview of how academic supervision is carried out as an effort to foster the professional competence of early childhood education teachers (PAUD). The success of a quality learning process relies heavily on the role of the teacher as an element of the teaching staff without the exception of PAUD teachers. PAUD teachers are required to have the ability or competence in carrying out their profession as professional teachers. The competencies in question include pedagogic competence, personality competence, professional competence and social competence. Academic supervision activities are used as the most appropriate approach in conducting coaching efforts to assist PAUD teachers in developing their professional competencies. The function of academic supervision activities is a tool to effectively manage PAUD learning. In academic supervision activities, the Principal acts as a supervisor who continuously provides guidance in the form of observations, assessments, directives, guidance and assistance to PAUD teachers. Abstrak Artikel ini bertujuan untuk memberikan gambaran tentang bagaimana supervisi akademik dilakukan sebagai upaya pembinaan kompetensi profesional guru pendidikan anak usia dini(PAUD).Keberhasilan proses pembelajaran yang berkualitas sangat bergantung pada peran guru sebagai unsur tenaga pendidik tanpa terkecuali bagi guru PAUD.Guru PAUD dituntut untuk memiliki kemampuan atau kompetensi dalam menjalankan profesinya sebagai guru yang profesional.Kompetensi yang dimaksud meliputi kompetensi pedagogik, kompetensi kepribadian, kompetensi profesional dan kompetensi social.Kegiatan supervisi akademik digunakan sebagai suatu pendekatan yang paling tepat dalam melakukan upaya pembinaan untuk membantu guru PAUD dalam mengembangkan kompetensi profesionalnya.Fungsi dari kegiatan supervisi akademik ini sebagai alat untuk mengelola pembelajaran di PAUD secara efektif.Pada kegiatan supervisi akademik, Kepala sekolah bertindak sebagai supervisor yang secara berkelanjutan memberikan pembinaan berupa pengamatan, penilaian, arahan, bimbingan dan bantuan kepada guru PAUD. Kata Kunci: Profesi guru, kompetensi profesional, supervisi akademik